Conceptualization and Operationalization of Certification in the US and Canadian Nursing Literature. (May 2018) - Chappell, Kathy; ElChamaa, Rima; Jeong, Dahn; Kendall-Gallagher, Deborah; Salt, Elizabeth; Reeves, Scott; Moore, Donald; Olson, Curtis; Van Hoof, Thomas; Lundmark, Vicki; Danilovich, Natalia; Kitto, Simon
Abstract : OBJECTIVE: To identify how certification is defined, conceptualized, and discussed in the nursing literature. BACKGROUND: Although it is hypothesized that credentialing is associated with better patient outcomes, the evidence is relatively limited. Some authors have suggested that the lack of consistency used to define certification in nursing literature may be one of the dominant obstacles in credentialing research. METHODS: This scoping review was guided by Arksey and O'Malley's framework, and quantitative and qualitative analyses were conducted. RESULTS: The final data set contained a total of 36 articles, of which 14 articles provided a referenced definition of certification. Thematic analysis of the definitions yielded 8 dominant themes. CONCLUSION: The lack of a common definition of certification in nursing must be addressed to advance research into the relationship between certification processes in nursing and healthcare outcomes.